(untitled) (Swiss Medical Weekly, 2014)
OBJECTIVES: Despite new treatment modalities, cyclophosphamide (CYC) remains a cornerstone in the treatment of organ or life-threatening vasculitides and connective tissue disorders. We aimed at analysing the short- and long-term side-effects of CYC treatment in patients with systemic autoimmune diseases. METHODS: Chart review and phone interviews regarding side effects of CYC in patients with systemic autoimmune diseases treated between 1984 and 2011 in a single university centre. Adverse events were stratified according to the “Common Terminology Criteria for Adverse Events” version 4. RESULTS: A total of 168 patients were included. Cumulative CYC dose was 7.45 g (range 0.5–205 g). Gastro-intestinal side effects were seen in 68 events, hair loss occurred in 38 events. A total of 58 infections were diagnosed in 44/168 patients (26.2%) with 9/44 suffering multiple infections. Severity grading of infections was low in 37/58 cases (63.8%). One CYC-related infection-induced death (0.6%) was registered. Amenorrhoea occurred in 7/92 females (7.6%) with 5/7 remaining irreversible. In females with reversible amenorrhoea, prophylaxis with nafarelin had been administered. Malignancy was registered in 19 patients after 4.7 years (median, range 0.25–22.25) presenting as 4 premalignancies and 18 malignancies, 3 patients suffered 2 premalignancies/malignancies each. Patients with malignancies were older with a higher cumulative CYC dose. Death was registered in 28 patients (16.6%) with 2/28 probably related to CYC. CONCLUSIONS: Considering the organ or life-threatening conditions which indicate the use of CYC, severe drug-induced health problems were rare. Our data confirm the necessity to follow-up patients long-term for timely diagnosis of malignancies. CYC side-effects do not per se justify prescription of newer drugs or biologic agents in the treatment of autoimmune diseases.